Stakeholders Theory and Its effects on Organization's Technological Change - Alsbaity, Maryam Abdalrazaq (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2018)
This paper intends to investigate the effectiveness of the Stakeholders Theory in the organizational process of Technological change. It focuses on the importance of involving every stakeholder in the decision-making process. This focal point will be interpreted through integrating the Systems Theory with the organization's adaptive stage. It also shows how the Board of Directors (hereinafter, BODs)1and the executives manage this change and apply leadership skills when dealing with each stakeholder. This research deploys the stakeholders theory specifically focusing on shareholders, investors, management, employees and customers. The anticipated findings indicate that the application of governance theories and specially stakeholders theory is highly impactful. This paper intends to compare the typical outcomes based on literature with outcomes based on real life applications of organizational technological change. It shall be interpreted through a selection of change management models, CVC2 analysis and technological change models. Moreover, measurements of the outcomes for each stakeholder's participation will be presented through (e.g. employees performance, ROI3, etc.).